The Modeling of the Electric Heating and Cooling System of the Integrated Energy System in the Coastal Area - Zuo, Xue; Dong, Mingyu; Gao, Fengkai; Tian, Shiming (Journal of coastal research, 2020)
Zuo, X.; Dong, M.; Gao, F., and Tian, S., 2020. The modeling of the electric heating and cooling system of the integrated energy system in the coastal area. In: Yang, Y.; Mi, C.; Zhao, L., and Lam, S. (eds.), Global Topics and New Trends in Coastal Research: Port, Coastal and Ocean Engineering. Journal of Coastal Research, Special Issue No. 103, pp. 1022–1029. Coconut Creek (Florida), ISSN 0749-0208. The accurate analysis of the coupling relationship of the electric heating and cooling system is the basis of its load calculation. Because the current method does not consider the analysis of the coupling relationship of the electric heating and cooling system in the design, the accuracy of the load calculation results is low. In order to solve this problem, the load modeling of the electric heating and cooling system of the comprehensive energy system in the coastal area is studied. Through the calculation of power network, natural gas network and comprehensive energy flow, the power flow value of electric heating and cooling system of comprehensive energy system is obtained. On this basis, according to the energy conversion efficiency of the equipment included in the energy hub and the distribution ratio of electric energy and gas, the coupling relationship of the electric heating and cooling system is obtained. According to the coupling relationship of the electric heating and cooling system, the load model of the electric heating and cooling system is constructed, and the optimal solution of the model is calculated by Grey Wolf algorithm to complete the modeling research of the electric heating and cooling system of the comprehensive energy system in the coastal area. The simulation results show that the model designed in this paper can obtain the accurate calculation results of the active power and reactive power of the electric heating and cooling system, and the calculation of the load of the electric heating and cooling system is time-consuming, accurate and reliable.